Importance of Trividh Kukshiya Matravat Aahara in Relation to Digestion of the Food - Manjiri Palnitakar Bhende,; Prachi Dwarkaprasad Walde, (International Journal of Ayurveda and Pharma Research, 2021)
According to Ayurveda food is one of the significant factors for health as well as source for diseases i.e., wholesome food is responsible for pleasure and unwholesome food is responsible for unhappiness. Alongside the quality of food, the quantity of food is also a lot of significant that how it is taken, on the grounds that food taken in ill-advised manner can prompt various diseases. Digestion of food is considered as one of the most important physiologic processes in our body to be of prime significance in conserving health. A nutritious eating regimen won't have the most extreme effect in promoting health unless the digestive capacity is optimal. Balanced Agni (digestive fire) is basic for appropriate digestion of food, for this reason the idea of Matravat ahara ought to be considered as portrayed in Trividhkukshiya viman adhyay. For proper digestion of food, it should be consumed in appropriate quantity as described in Trividh kukshiya adhyaya, where it is specifying that, stomach capacity is divided into 3 parts: One part of it is filled up with solid food, the second part with liquids and the third part is left for Vata, Pitta and Kapha. Thus, the good quality food taken in appropriate amount will nourish the tissue elements of the body along with mind and senses only when it is properly digested. This article aimed to signify importance of Trividh kukshiya matravata aahara for proper digestion.